Pesantren in Indonesia and Sustainable Development Issues - Syahdatul Maulida; Mohammad Mahbubi Ali (The Economic Review of Pesantren, 2023)
This paper aims to observe the evolution of research focusing on Pesantren and sustainable development issues published in various journals around the world. The method used is a qualitative approach with bibliometric analysis using R software. The data used are secondary data related to the theme "Pesantren and sustainable development" obtained from the Dimensions database. A total of 57 documents covering the period from 2001 to October 2023 were used in the analysis. The results showed that the trend in the number of documents examining Pesantren and sustainable development issues tends to increase, reaching its peak in 2023 with a total of 15 documents. In addition, the number of articles published per year and the average citations per year are also relatively low, indicating a lack of attention to this topic in the academic world. However, Pesantren practices in order to support sustainable development continue to be intensively carried out, especially in Indonesia. This is done through various mechanisms such as empowering productive waqf for Pesantren as an economic development strategy, empowering MSMEs and entrepreneurship in communities around Pesantren, eco-Pesantren as an effort to contribute to environmental preservation, and developing santripreneurs and Pesantren entrepreneurship.